46+2=3(5x+1)

Simple and best practice solution for 46+2=3(5x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 46+2=3(5x+1) equation:


Simplifying
46 + 2 = 3(5x + 1)

Combine like terms: 46 + 2 = 48
48 = 3(5x + 1)

Reorder the terms:
48 = 3(1 + 5x)
48 = (1 * 3 + 5x * 3)
48 = (3 + 15x)

Solving
48 = 3 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
48 + -15x = 3 + 15x + -15x

Combine like terms: 15x + -15x = 0
48 + -15x = 3 + 0
48 + -15x = 3

Add '-48' to each side of the equation.
48 + -48 + -15x = 3 + -48

Combine like terms: 48 + -48 = 0
0 + -15x = 3 + -48
-15x = 3 + -48

Combine like terms: 3 + -48 = -45
-15x = -45

Divide each side by '-15'.
x = 3

Simplifying
x = 3

See similar equations:

| (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 | | -38-8x=-3(-6+5x) | | 4+12x=4+x | | 2x^2y+xy-100=0 | | 4+x=3x-2 | | 3.2+6=6m-15 | | 5m=8m-15 | | -(r-5-8p)= | | 4M+3M=12 | | 8(5+13x)-(-2x+8)=32 | | -7x+2.3=7x-7.9 | | -14-(-3)= | | -28+8x=4-6(2-2x) | | x^2+kx+(k+1)=0 | | 14(12k-12)+14(-10k-11)=42 | | -2.5x+18-1.6x=57 | | 30-4n=-(n-6) | | -2(2t+8)=-28 | | (4x-4)(3x-7)= | | -52=a-11 | | 14+(4p+46)+0= |

Equations solver categories